Fine interpretation method for tight reservoirs based on core experiments and imaging logging: a case study of tight carbonate rocks in L area - Dan, Li; Kui, Wu; Yu, Qi; Shanshan, Yu (Frontiers in Earth Science, 2025)
IntroductionWith the gradual reduction in conventional exploration and the gradual improvement of hydraulic fracturing technology, the exploration of tight oil and gas has gradually become general. Marine carbonate rocks are developed in the lower Paleozoic Ordovician in the eastern margin of Ordos Basin. According to the drilling results, the minerals in this area are mainly calcite and dolomite, and the secondary minerals are halite, anhydrite, quartz, feldspar and clay minerals. Core experiment reveals that the reservoir is tight, with porosity between 2 and 6% and permeability less than 2mD. Relationship between lithology and porosity established by conventional logging interpretation is not consistent with the results of gas logging, so it is impossible to accurately determine the reservoir location.MethodThe research in this paper is to interpret lithologic profile based on mineral X-ray diffraction data, to accurately evaluate pore type and permeability based on borehole electrical imaging and multipole array acoustic logging, and to interpret gas saturation by using the Archie formula with variable cementation index.Results and discussionThis method improves the interpretation accuracy of geophysical logging methods for tight reservoirs in this block, and plays a key role in favorable evaluation of reservoir sweet spots.